Implementasi Load Balancing Per address connection ECMP Algoritma Round Roubin Mikrotik Router - Ahmad Fauzi; Dwi Yuni Utami (Universitas Medan Area, 2022)
Internet access is a basic need that must be owned by both individuals and companies because of how important internet access is so that a company can work, in the current digital era, when internet access for a company or individual is experiencing problems, due to the ISP (Internet Service Provider). If the network is down or disconnected, it can be said that all activities will be inefficient, hampered, cannot open email, cannot connect to the central server, even entrepreneurs with orders via online cannot sell, for that when internet access becomes a vital object for companies, it is necessary an internet access or more than one ISP can use two or more ISPs where many methods are used to combine two or more internet accesses into one network that is connected by a local network but a very good method is used to maximize the two or more ISPs a is to use the Load Balancing method using the ECMP round roubin algorithm on the Mikrotik router device so it is hoped that internet access will continue even though one of the ISPs is down or network disturbances.